(untitled) (Konturen, 2013)
Beginning with a comparison of Joseph Conrad’s Heart of Darkness and certain paintings of Piet Mondrian, this essay explores the inherent abstraction of Romantic precursors to those Modernist literary and painterly compositions that (continue to) place a subject squarely before an expanse (of water, of light, or of dark).